Analysis of air flow and heat transfer in a winding using porous medium approach. (March 2020) - Kholghi, S. Ali; Hanafizadeh, Pedram; Karbalaee M., Sina; Ashjaee, Mehdi
Abstract: The efficient cooling of turbo-generators especially in the end-windings region directly affects the power output rating. Modeling the coolant flow passing through the stator end-winding of a high-powered generator, however, remains a challenge due to a large number of parts with irregular geometries as well as the intricacy of cooling flow paths. This paper focuses on a numerical investigation of flow and heat transfer in stator end-winding aiming at replacing the geometry of winding with a porous medium model. Using computational fluid dynamics analysis to examine the viscous and inertial contributions to the pressure drop of airflow in the stator end-winding region, a generalized porous medium model is developed for the real physical geometry of winding together with a correlation for interfacial Nusselt number. The results indicate that the inertial effect considerably prevails over the viscous effect, that is, viscous contribution becomes small and almost negligible. It is shown that not only the pressure drop characteristics match closely within both real and porous models, but also the heat transfer results agree as well which means that the replaced porous model can amply describe the macroscopic behavior of the winding.